Simulation of the sensing mechanism in quantum dot gas sensor by quantum light harvesting approach - Suntijitrungruang, Ongart; Lakronwat, Jidapa; Uthailiang, Teerapat; Pongkitiwanichakul, Peera; Boonchui, S. (Frontiers in Chemistry, 2022)
Quantum dot (QD) gas sensors are one of the useful nanotechnology applied to protect unnecessary harm for people. This work explores the mechanism in QD gas sensors theoretically in order to advance prudent design of relevant products. The theoretical model employed in this research is similar to the process in the plant’s photosynthesis referred to as charge separation of light harvesting. In this work, we investigate the details of energy transport in QD gas sensors carried by electrons from the circuit. We demonstrate theoretically how the effects of the temperature and gas detection affect the electron transport. To analyze thoroughly, the potential energy referred to as Schotthy barrier perturbed by gasses is considered. Moreover, the energy transfer efficiency (ETE) of QD gas sensors for oxidizing or reducing gas are showed in the simulation. The results imply that the electron transport between QDs (raising the current and lessening the current) depends on a parameter corresponding with Schotthy barrier. In regard to thermal energy portrayed by phonon baths, the higher temperature shortens the time duration of energy transport in QDs, hence raising energy transfer efficiency and energy current. Our model can be applied for QD gas sensor’s design and manufacture further.